Pattern of Skin Diseases in University Students Presenting in Out Patient Department of University of Lahore Teaching Hospital (Medical Forum Monthly, 2021)
Objective: To assess the pattern of skin diseases in patients and to determine their relation with demographic characteristics.Study Design: Cross sectional study.Place and Duration of Study: This Study was conducted at the Dermatology Department at University of Lahore from January 2019 to December 2019.Materials and Methods: One thousand, nine hundred and ninety-two students were enrolled.Results: In our study 1308 (65.7%) were females and 684 (34.3%) were males with M:F ratio 1.0:1.9. According to age the participants were divided into 3 groups. Late-teens: total 610 (30.6%) of total participants) 473 (23.7%) were females and 137(7%) were males. Early -twenties: The largest group comprising of 51% of total participants total 1018, (51%); 629 (31.5%) were females and 389 (19.5%) males. Mid-twenties: the smallest group total364 (18.2%): 206 (10.3%) were females and 158 (8%) were malesConclusion: Acne vulgaris is the most common lesion seen in the OPD with females being most likely affected gender. Stress, hormonal, dietary factors, sedentary life style play a vital in the causation and progression of dermatoses.